2005
DOI: 10.1242/jcs.01728
|View full text |Cite|
|
Sign up to set email alerts
|

STAT-1 facilitates the ATM activated checkpoint pathway following DNA damage

Abstract: STAT-1 plays a role in mediating stress responses to various stimuli and has also been implied to be a tumour suppressor. Here, we report that STAT-1-deficient cells have defects both in intra-S-phase and G2-M checkpoints in response to DNA damage. Interestingly, STAT-1-deficient cells showed reduced Chk2 phosphorylation on threonine 68 (Chk2-T68) following DNA damage, suggesting that STAT-1 might function in the ATM-Chk2 pathway. Moreover, the defects in Chk2-T68 phosphorylation in STAT-1-deficient cells also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 50 publications
5
53
0
2
Order By: Relevance
“…Townsend and colleagues have also reported enhanced Stat1 expression in p53-KO (22). It is well known that radiation-induced ATM activation leads to the accumulation of p53.…”
Section: Discussionmentioning
confidence: 89%
“…Townsend and colleagues have also reported enhanced Stat1 expression in p53-KO (22). It is well known that radiation-induced ATM activation leads to the accumulation of p53.…”
Section: Discussionmentioning
confidence: 89%
“…In case DNA repair is not possible, these checkpoints initiate apoptosis to remove damaged cells. 39 Another report demonstrated that STAT1 is required for the transcriptional up-regulation of 2 important mediators of ATM checkpoint activation, 53BP1 and MDC1, 42 suggesting the hypothesis that STAT1 can enhance the action of DNAdamaging drugs by its influence on the ATM checkpoint pathway.…”
Section: Discussionmentioning
confidence: 99%
“…2). This could be the result of a defective ATM checkpoint pathway, requiring STAT1 signaling, 42 leading to an increased accumulation of drug-induced mutations. It remains to be seen whether these patients experience a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although Bcl-xl and XIAP are bona fide antiapoptotic proteins, p27 Kip1 may also contribute to survival by inhibiting cell cycle progression and blocking the effects of chemotherapeutic drugs that are effective in proliferating cells (66). Some studies, however, indicated that Stat1 can act as a checkpoint in DNA-damaging chemotherapies and synergize with either p53 or IFNs to induce cell death in response to doxorubicin treatment (67)(68)(69). Stat1 function in cell survival as well as cell death may be explained by its ability to respond to drugs via pathways that are controlled by its phosphorylation in a temporal fashion.…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 99%